2019
DOI: 10.3390/app9132693
|View full text |Cite
|
Sign up to set email alerts
|

Application Study of Adaptive Tracking Algorithm in Active Noise Control System of Transformer

Abstract: Active noise control (ANC) technology can be able to reduce the low frequency noise effectively, and has been widely applied in limited enclosed equipment, such as cars, aircraft cockpits, and headphones, etc. Compared with the traditional noise reduction methods, ANC technology is a cost-effective method in handling the low-frequency noise of transformers. An experimental ANC system in a virtual substation is designed and constructed. An adaptive signal tracking ANC algorithm is proposed, and a set of ANC exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The acoustics wave propagation can be described in term of first order differential equations where the temporal derivative of one field is related to the spatial derivative of another field as in the following Eqs. ( 14) and (15).…”
Section: Finite Difference Time Domain (Fdtd) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustics wave propagation can be described in term of first order differential equations where the temporal derivative of one field is related to the spatial derivative of another field as in the following Eqs. ( 14) and (15).…”
Section: Finite Difference Time Domain (Fdtd) Methodsmentioning
confidence: 99%
“…Three years later, Efron and Han proposed the extension from his own work with Graupe on a single point adaptive ANC to address the problem of wide-area noise cancellation [10]. Currently, many research relevant to a wide-area-like ANC applications have been published in various aspects, for example, Gunnar Gäbel proposed the development and implementation of a multi-channel ANC system for the reduction of road induced vehicle interior noise [11], Liu and Kuo proposed the use of microphone array in wide area simulations [12], Iwai, Hase and Kajikawa tried to identify the optimal reference microphone array based on time difference arrival (TDOA) technique [13], Jianjun, Bhan, Dongyuan and Woon presented the leverage of an underdetermined system in a multi-channel ANC for open windows in a large space [14], Ying, Wang and Liu presented the application study of an adaptive tracking algorithm in the ANC system for lower the transformer noise in the substation specific area [15], Zhang, Qin, Zou and Qiu presented the secondary source consideration and error sensing strategies for the ANC of sound transmission through a small opening in a wall [16], Munir and Abdulla proposed new ANC algorithms to deal with acoustic domain in silencing a remote location quiet zone called FxLMS algorithm in 2020 [17]. Some researchers attempted to create a quiet zone in specific area like closed room using sparse decomposition of reference signals from distributed sensors arranged in term of circular arrays to reduce broadband noise fields [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ostiguy et al [16] recently tested the efficacy of flexible acoustical blankets applied to the case of a 125 kV transformer, showing excellent results. Wang et al [17] proposed a combination of a traditional barrier with 3D-printed acoustic metamaterial and an active noise control system, obtaining promising results from simulations. Active control is indeed another noise control option that can be used to abate noise from transformers, as reviewed by Zou et al [18] and by Qiu et al [19] and as demonstrated by the positive results shown by in-field applications [17,20,21].…”
Section: Introductionmentioning
confidence: 99%